Chapter 2. Screening and use of nutritional and health-related benefits of the main crops - Ibba, Maria Itria; Palacios-Rojas, Natalia; Rosales-Nolasco, Aldo (Elsevier, 2023)
Wheat, maize, rice, and barley play a critical role in the human diet, contributing to most of the calories and protein intake worldwide. This is mainly because of their higher productivity, storability, adaptability to different climate conditions, accessibility, and affordability, compared to other crops. However, even if food production has grown in the past years, nutrient deficiency is currently posing a serious threat, with millions of people suffering from malnutrition every year. Additionally, consumption of some cereals has been associated with adverse health reactions which affect 1%–10% of the world population. For these reasons, nutritional quality improvement of cereal grains has become a major target for all the stakeholders participating in cereal food production. Thus several breeding programs worldwide have been focusing on developing nutritionally enriched grains. This chapter will present the recent progress obtained in micronutrient biofortification (minerals, provitamin A, and anthocyanins), dietary fibers’ improvement, and modulation of protein content and quality in four major staple crops, wheat, maize, rice, and barley, using nontransgenic approaches. The feasibility of using natural variations, induced mutations, or other approaches involving genomic manipulation will also be discussed.